Pengeksekusian Rahasia Dagang Sebagai Objek Jamina dalam Perbankan - Ni Nyoman Indah Pratiwi; Ryka Yuliana (Jurnal Ilmiah Kebijakan Hukum, 2023)
Laws and regulations related to trade secrets do not explicitly stipulate that trade secrets can be used as an object of guarantee in banking, causing legal uncertainty for the public and affecting the condition of trade secrets being used as collateral objects and the execution of goods for certain reasons. Writing this article aims to examine and analyze the regulation of trade secrets as an object of guarantee and the execution of trade secrets in the banking. Then, through this article it can provide benefits in the form of juridical understanding related to trade secret legal arrangements as objects of collateral in the banking, contribute literature, and can be considered by the government in establishing laws and regulations related to trade secrets as collateral objects. The legal issue in the form of a veil of norms makes this article use normative legal research methods using a statutory and contextual approach, followed by legal materials in the form of primary, secondary and tertiary legal materials. The results of the study show that trade secrets can be used as collateral in the banking because they have economic value, can be transferred, and have no time limit as long as they are kept confidential. Then related to the execution of trade secrets can be carried out based on the execution of fiduciary guarantees considering that trade secrets can be charged with fiduciary guarantees. The method of execution is through executorial titles, public auctions, and private sales as stipulated in Article 29 of the Fiduciary Guarantee Law. Trade secrets as an object of guarantee have been explicitly regulated and execution of trade secrets can be carried out through private sales and auctions as regulated in the German Lending and Taking Security Act. Based on this explanation, the solution to the legal issues in this article is that Indonesia can amend the Trade Secrets Law by considering German Legislation so as to provide legal certainty for the Indonesian people regarding trade secrets as an object of guarantee.